Ovothiol ensures the correct developmental programme of the sea urchin Paracentrotus lividus embryo - Alfonsina Milito; Maria Cocurullo; Alfredo Columbro; Simona Nonnis; Gabriella Tedeschi; Immacolata Castellano; Maria Ina Arnone; Anna Palumbo (Open Biology, 2022)
Ovothiols are π-methyl-5-thiohistidines produced in great amounts in sea urchin eggs, where they can act as protective agents against the oxidative burst at fertilization and environmental stressors during development. Here we examined the biological relevance of ovothiol during the embryogenesis of the sea urchin Paracentrotus lividus by assessing the localization of the key biosynthetic enzyme OvoA, both at transcript and protein level, and perturbing its protein translation by morpholino antisense oligonucleotide-mediated knockdown experiments. In addition, we explored the possible involvement of ovothiol in the inflammatory response by assessing ovoA gene expression and protein localization following exposure to bacterial lipopolysaccharide. The results of the present study suggest that ovothiol may be a key regulator of cell proliferation in early developing embryos. Moreover, the localization of OvoA in key larval cells and tissues, in control and inflammatory conditions, suggests that ovothiol may ensure larval skeleton formation and mediate inflammatory processes triggered by bacterial infection. This work significantly contributes to the understanding of the biological function of ovothiols in marine organisms, and may provide new inspiration for the identification of the biological activities of ovothiols in humans, considering the pharmacological potential of these molecules.